Information content on hydrometeors from millimeter and sub-millimeter wavelengths. Issue 1 (1st January 2017) - Birman, Camille; Mahfouf, Jean-François; Milz, Mathias; Mendrok, Jana; Buehler, Stefan A.; Brath, Manfred
ABSTRACT: This study examines the information content on hydrometeors that could be provided by a future HYperspectral Microwave Sensor (HYMS) with frequencies ranging from 6.9 to 874 GHz (millimeter and sub-millimeter regions). Through optimal estimation theory the information content is expressed quantitatively in terms of degrees of freedom for signal ( DFS ). For that purpose the Atmospheric Radiative Transfer Simulator (ARTS) and its Jacobians are used with a set of 25 cloudy and precipitating profiles and their associated errors from the European Centre for Medium-range Weather Forecasting (ECMWF) global numerical weather prediction model. In agreement with previous studies it is shown that frequencies between 10 and 40 GHz are the most informative ones for liquid and rain water contents. Similarly, the absorption band at 118 GHz contains significant information on liquid precipitation. A set of new window channels (15.37-, 40.25-, 101-GHz) could provide additional information on the liquid phase. The most informative channels on cloud ice water are the window channels at 664 and 874 GHz and the water vapour absorption bands at 325 and 448 GHz. Regarding snow water contents, the channels having the largest DFS values are located in window regions (150-, 251-, 157-, 101-GHz). However it is necessary to consider 90 channels in order to represent 90% of the DFS . The added value of HYMS has been assessed against current Special Sensor Microwave Imager/Sounder (SSMI/S) onboard the Defense Meteorological Satellite Program (DMSP) and future (Microwave Imager/Ice Cloud Imager (MWI/ICI) onboard European Polar orbiting Satellite – Second Generation (EPS-SG)) microwave sensors. It appears that with a set of 276 channels the information content on hydrometeors would be significantly enhanced: the DFS increases by 1.7 against MWI/ICI and by 3 against SSMI/S. A number of tests have been performed to examine the robustness of the above results. The most informative channels on solid hydrometeors remain the same over land and over ocean surfaces. On the other hand, the database is not large enough to produce robust results over land surfaces for liquid hydrometeors. The sensitivity of the results to the microphysical properties of frozen hydrometeors has been investigated. It appears that a change in size distribution and scattering properties can move the large information content of the channels at 664 and 874 GHz from cloud ice to solid precipitation.